PEMANFAATAN MEDIA GAMBAR DALAM PEMBELAJARAN BAHASA INDONESIA UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS II SDIT QURRATA A’YUN 3 BATUSANGKAR - Bunga Zulfa Idris; Al Amin (CV. Adiba Aisha Amira, 2025)
This examine aims to explain the usage of photo media in teaching Indonesian language and to examine how such media can beautify the gaining knowledge of interest of 2d-grade college students at SDIT Qurrata A’yun three Batusangkar. The research employed a descriptive qualitative technique with the Indonesian language trainer and 2nd-grade students because the research subjects. statistics had been accrued through observation, interviews, and documentation. The findings display that photo media have been correctly utilized by the instructor via engaging visual displays, interactive thinking, and storytelling sports based on snap shots. using photo media become observed to boom college students’ mastering hobby, as indicated through emotions of leisure, attention, curiosity, and energetic participation at some point of the learning technique. supporting elements protected attractive visible illustrations and the suitability of the media with students’ developmental tiers, while demanding situations worried barriers in photograph length and educational time. consequently, photo media function an effective academic tool for reinforcing the mastering interest of fundamental faculty students.